NON VERBAL SYMBOLIC MODE IN KEBO-KEBOAN CEREMONY IN DUSUN KRAJAN KABUPATEN BANYUWANGI - WULANDARI, LINDA ASTRI DWI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Astri, Linda. 2014. Non-Verbal Symbolic Mode in Kebo-keboan Ceremony in Dusun Krajan  Kabupaten Banyuwangi.  Study Program of English, Language and Literature Department, Faculty of Cultural Studies. Universitas  Brawijaya. Supervisor:Winda Candra Hantari;Co-supervisor: Aris SiwantiKeywords:  Non-verbal symbolic mode, connotation, denotation, mythology, BlambanganRitual ceremony contains many symbols as the reflection of feelings, emotions, attitudes, and myth in the society. Semiotics is deeply concerned about signs including symbol, icon, and index that can be found in daily phenomenon of human environment. The symbols represent the communication between culture and society is very interesting to investigate as the semiotic analysis. This study was conducted to discover non-verbal symbolic mode in Kebo-keboan ceremony in Dusun Krajan Kabupaten Banyuwangi and mythology which is influenced that symbols.    This study uses qualitative approach focused on the phenomena being studied. Content analysis as the type of the research because it analyzed the data obtained from the observation of  Kebo-keboan  ceremony 2013 and in-depth interview with some people who know well about the ritual ceremony, such as the Culture Expert of Banyuwangi to get some data based on the research problem.   There are three classifications of non-verbal symbol found in Kebo-keboan ceremony. Those are physical objects (subjects or actors of  Kebo-keboan ceremony and supporting equipment), behaviors (the action and the movement of the parade of  Kebo-keboan  in  Ider  Bumi); and setting (time, location, atmosphere). Moreover the interpretation of symbol found in  Kebo-keboan ceremony can be conducted in denotation and connotation theory by Roland Barthes. The mythologies in Dusun Krajan also influenced the interpretation of non-verbal symbolic mode in Kebo-keboan ceremony.    The suggestion for the next study is to have a good time management during research field to get the deep information. Furthermore, the next study better to conduct both verbal and non-verbal symbolic mode of myth to get the whole meaning of Kebo-keboan ceremony.